LATE HOLOCENE SEDIMENTATION IN ACTIVE GEOLOGICAL STRUCTURES OF THE CHUKCHI SEA - E. G. Vologina; I. A. Kalugin; A. V. Dar’in; A. S. Astakhov; M. Sturm; G. P. Chernyaeva; N. V. Kulagina; A. N. Kolesnik (Геодинамика и тектонофизика)
The article presents the detailed analysis results considering bottom sediments from the Chukchi Sea. Two core samples, b16 and НС–8 were taken from the northern Herald Canyon 150 km northeast from NE Wrangel Island. Core b16 has been studied in more detail. According to the 210Pb measurements, the recent sedimentation rate amounts to 0.9 mm/y–1 at the sampling point. In the bottom layer of the core sample, the minimum concentrations of biogenic components (SiO2bio, Corg, Ntot, and Br) and the increased concentrations of cold-water diatom species Thalassiosira antarctica may result from low biological productivity during the Maunder Minimum. A correlation with recent global warming (11–22 years) is shown by the increased concentrations of SiO2bio, Corg, Ntot, and Br and the decreased values of magnetic susceptibility and X-ray density in the top layer (1–2 cm) of the same core sample. The results of our geochemical and diatom analysis support the available literature data and confirm that the Late Holocene sedimentation in the Chukchi Sea takes place in the zone wherein the water transits from the Pacific to the Arctic Ocean.